Enhanced Near‐Infrared Photoresponse of Inverted Perovskite Solar Cells Through Rational Design of Bulk‐Heterojunction Electron‐Transporting Layers - Chen, Chih‐I; Wu, Shengfan; Lu, Yen‐An; Lee, Chia‐Chen; Ho, Kuo‐Chuan; Zhu, Zonglong; Chen, Wen‐Chang; Chueh, Chu‐Chen (Advanced science, 2019)
How to extend the photoresponse of perovskite solar cells (PVSCs) to the region of near‐infrared (NIR)/infrared light has become an appealing research subject in this field since it can better harness the solar irradiation. Herein, the typical fullerene electron‐transporting layer (ETL) of an inverted PVSC is systematically engineered to enhance device's NIR photoresponse. A low bandgap nonfullerene acceptor (NFA) is incorporated into the fullerene ETL aiming to intercept the NIR light passing through the device. However, despite forming type II charge transfer with fullerene, the blended NFA cannot enhance the device's NIR photoresponse, as limited by the poor dissociation of photoexciton induced by NIR light. Fortunately, it can be addressed by adding a p‐type polymer. The ternary bulk‐heterojunction (BHJ) ETL is demonstrated to effectively enhance the device's NIR photoresponse due to the better cascade‐energy‐level alignment and increased hole mobility. By further optimizing the morphology of such a BHJ ETL, the derived PVSC is finally demonstrated to possess a 40% external quantum efficiency at 800 nm with photoresponse extended to the NIR region (to 950 nm), contributing ≈9% of the overall photocurrent. This study unveils an effective and simple approach for enhancing the NIR photoresponse of inverted PVSCs. A low bandgap nonfullerene acceptor (NFA) is incorporated into fullerene electron‐transporting layer (ETL) of an inverted perovskite solar cell aiming to intercept the NIR light passing through the device. However, it cannot enhance the device's NIR photoresponse. Further adding a p‐type polymer effectively enhances the device's NIR photoresponse due to better cascade energy‐level alignment and increased hole mobility.